2005
DOI: 10.1177/194589240501900516
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Total Intravenous Anesthesia Compared with Inhalational Anesthesia on the Surgical Field during Endoscopic Sinus Surgery

Abstract: In patients undergoing ESS, TIVA results in a better surgical field than inhalational anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
193
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(204 citation statements)
references
References 19 publications
9
193
2
Order By: Relevance
“…Eight studies compared the use of an intravenous analgesic drug to an inhaled agent: six prospective studies (17,20,23,25,27,28) and two retrospective studies (24,26) .…”
Section: D3) Studies Comparing Intravenous or Inhaled Central Nervousmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies compared the use of an intravenous analgesic drug to an inhaled agent: six prospective studies (17,20,23,25,27,28) and two retrospective studies (24,26) .…”
Section: D3) Studies Comparing Intravenous or Inhaled Central Nervousmentioning
confidence: 99%
“…To assess the VSF, most of the authors (2,12,(15)(16)(17)(19)(20)(21)(22)24,28) used the scale proposed by Fromme et al (18) and adapted the one described by Boezaart et al (19) . This assessment method is not sufficiently discriminatory.…”
Section: Can Preoperative Treatment Be Recommended?mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, FESS should be performed at a lower level of HR (20) as controlling HR is more effective on improving the surgical approach than lowering MAP. Compared with inhalation anesthesia, including isoflurane, sevoflurane, total intravenous anesthesia with propofol and remifentanil is able quickly and effectively to lower HR and MAP, reduce bleeding and provide an improved surgical approach (6)(7)(8)21,22). The reason for this is that inhalation anesthetics dilate blood vessels and cause reflex tachycardia (23).…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies have suggested that the intra-operative blood loss was reduced with propofol total intravenous anaesthesia (TIVA) compared to volatile agents. [16][17][18] However, more recent studies do not show significant difference. 19 Propofol has been shown to interact with the endocannabinoid system in the brain.…”
mentioning
confidence: 99%